(untitled) (Hekima Review, 2023)
Many people in Kenya are unaware of ecumenism and are often indifferent to other religions and denominations, especially in academic institutions. St. Paul’s University is one of the oldest institutions in Kenya, founded on ecumenical principles. This study shows how ecumenism was practised at St. Paul’s University and how similar institutions in Kenya can use it. This is achieved by conducting oral interviews with staff members, using books obtained from this University, and other literature. The article concludes that St. Paul’s University has vast experience in ecumenism, which would greatly benefit other academic institutions in Kenya.